The Improvement of Learning Outcomes of Elementary School Students in Islamic Religious Education through the Index Card Match Model - Titin Zunta; Khermarinah Khermarinah (Jurnal Indonesia Pendidikan Profesi Guru, 2026)
Background: Islamic Religious Education instruction in elementary schools should ideally be interactive and engaging, fostering deep conceptual understanding and the internalization of religious values. Objective: This study aims to implement and evaluate the effectiveness of the Index Card Match learning model in improving engagement and learning outcomes among fourth-grade students on the topic of Asmaul Husna at SDN 02 XIV Koto. Method: This study employed Classroom Action Research (CAR) across two cycles, using data collection techniques such as observation, interviews, learning outcome tests, and documentation. Data were analyzed using a mixed-methods approach: qualitative descriptive analysis to describe learning activities and quantitative analysis to measure improvements in student achievement. Result: The findings indicate a significant increase from the pre-cycle to cycle II, with mastery learning improving from 25% to 80%, along with consistent growth in student participation and motivation in each meeting. Conclusion: The Index Card Match model is effective in enhancing student engagement, conceptual understanding, and Islamic Religious Education learning outcomes, particularly in the Asmaul Husna material. Contribution: This study strengthens the empirical evidence on the effectiveness of game-based cooperative learning models in Islamic Religious Education and provides practical recommendations for teachers to implement active learning strategies aligned with the developmental characteristics of elementary school students.